Higher oxidative balance score is associated with a decreased risk of infertility: an analysis of NHANES 2013–2020 - Ma, Mingjun; Xu, Huanying; Wang, Kexin; Chen, Yanfen; Pan, Ting; Zhu, Qiaoling (Frontiers in Nutrition, 2025)
BackgroundOxidative stress plays a crucial role in the female reproductive system. The oxidative balance score (OBS) is a new measure for assessing the balance between antioxidant and pro-oxidative factors in diet and lifestyle. However, limited studies have explored the relationship between OBS and infertility.MethodsWe performed a cross-sectional study including 2,664 women aged 20–45 years, based on data from the 2013–2020 National Health and Nutrition Examination Survey (NHANES). The OBS was derived from 16 dietary components and 4 lifestyle factors. We used multivariate logistic regression analysis to examine the association between OBS and infertility.ResultsThe analysis revealed a significant negative association between higher OBS and infertility risk, with an odds ratio (OR) of 0.98 (95% CI, 0.95–1.00) after full adjustment. Compared to the first quartile of OBS, the second, third, and fourth quartiles showed ORs of 0.71 (95% CI, 0.45–1.11), 0.79 (95% CI, 0.51–1.22), and 0.57 (95% CI, 0.35–0.92), respectively. Similarly, women in the highest dietary OBS and lifestyle OBS quartiles had a lower infertility risk compared to those in the lowest quartiles, with ORs of 0.60 (95% CI, 0.39–0.94) and 0.54 (95% CI, 0.32–0.93), respectively. Furthermore, subgroup analysis indicated that the association between the fourth quartile of OBS and infertility remained consistent, except among women with other ethnicities—including multi-racial, and college graduate or higher.ConclusionThese findings suggest that high dietary OBS and lifestyle OBS are associated with a lower risk of infertility.